Characterization of Histone Deacetylase Mechanisms in Cancer Development - Hai, Rihan; He, Liuer; Shu, Guang; Yin, Gang (Frontiers in Oncology, 2021)
Over decades of studies, accumulating evidence has suggested that epigenetic dysregulation is a hallmark of tumours. Post-translational modifications of histones are involved in tumour pathogenesis and development mainly by influencing a broad range of physiological processes. Histone deacetylases (HDACs) and histone acetyltransferases (HATs) are pivotal epigenetic modulators that regulate dynamic processes in the acetylation of histones at lysine residues, thereby influencing transcription of oncogenes and tumour suppressor genes. Moreover, HDACs mediate the deacetylation process of many nonhistone proteins and thus orchestrate a host of pathological processes, such as tumour pathogenesis. In this review, we elucidate the functions of HDACs in cancer.